A bioluminescence resonance energy transfer 2 (BRET2) assay for monitoring seven transmembrane receptor and insulin receptor crosstalk. (2nd November 2017) - Sanni, Samra Joke; Kulahin, Nikolaj; Jorgensen, Rasmus; Lyngsø, Christina; Gammeltoft, Steen; Hansen, Jakob Lerche
Abstract: The angiotensin AT1 receptor is a seven transmembrane (7TM) receptor, which mediates the regulation of blood pressure. Activation of angiotensin AT1 receptor may lead to impaired insulin signaling indicating crosstalk between angiotensin AT1 receptor and insulin receptor signaling pathways. To elucidate the molecular mechanisms behind this crosstalk, we applied the BRET 2 technique to monitor the effect of angiotensin II on the interaction between Rluc 8 tagged insulin receptor and GFP 2 tagged insulin receptor substrates 1, 4, 5 (IRS1, IRS4, IRS5) and Src homology 2 domain-containing protein (Shc). We demonstrate that angiotensin II reduces the interaction between insulin receptor and IRS1 and IRS4, respectively, while the interaction with Shc is unaffected, and this effect is dependent on Gαq activation. Activation of other Gαq-coupled 7TM receptors led to a similar reduction in insulin receptor and IRS4 interactions whereas Gαs- and Gαi-coupled 7TM receptors had no effect. Furthermore, we used a panel of kinase inhibitors to show that angiotensin II engages different pathways when regulating insulin receptor interactions with IRS1 and IRS4. Angiotensin II inhibited the interaction between insulin receptor and IRS1 through activation of ERK1/2, while the interaction between insulin receptor and IRS4 was partially inhibited through protein kinase C dependent mechanisms. We conclude that the crosstalk between angiotensin AT1 receptor and insulin receptor signaling shows a high degree of specificity, and involves Gαq protein, and activation of distinct kinases. Thus, the BRET 2 technique can be used as a platform for studying molecular mechanisms of crosstalk between insulin receptor and 7TM receptors.